Pushing the limits in order to avoid pneumonectomy - Maurizi, Giulio; Vanni, Camilla; Rendina, Erino Angelo (Journal of Thoracic Disease, 2019)
We have read with great interest the letter from Dr. Perentes and colleagues (1) with his comments about our recent paper (2). Dr. Perentes agrees with our results affirming that for the treatment of centrally located lung cancer sleeve lobectomy should be preferred over pneumonectomy even after induction treatment. Our paper included patients undergoing Y sleeve lobectomy after neoadjuvant chemotherapy.